Enhancing Third Graders' Understanding of the Water Cycle through Problem-Based Learning and Wordwall Integration - Auliya, Hafizhah Rahmiati; Adi, Banu Setyo; Rakhmawati, Sari; Suryani, Lilis; Haliem, Theresa Dwita; Pangastuti, Dindha (Jurnal Prima Edukasia, 2025)
Third-grade students often face difficulties in understanding the abstract and cyclical nature of the water cycle, leading to misconceptions and fragmented knowledge. This study aims to investigate the effectiveness of integrating Problem-Based Learning (PBL) and Wordwall (WW) in improving students’ conceptual understanding of the water cycle. A quasi-experiment employed in this study. The participants involved 105 third-grade students from one elementary school, divided into three groups: PBL+Wordwall, PBL-only, and a conventional instruction group. Over six sessions, students received instruction aligned with their group’s assigned strategy. The results, based on pretest and posttest comparisons analysed through t-tests and MANCOVA, show that both PBL and PBL+Wordwall outperform conventional teaching; however, PBL+Wordwall did not significantly surpass PBL alone. These findings suggest that PBL is a powerful strategy for teaching scientific concepts and that visual tools like Wordwall may offer added benefits in vocabulary reinforcement and engagement. This research supports the adoption of active learning and digital aids to enhance science instruction in elementary education.